PENJADWALAN PRODUKSI DI LINE B MENGGUNAKAN METODE CAMPBELL-DUDEK-SMITH (CDS) - Antoni Yohanes (Jurnal Ilmiah Dinamika Teknik, 2014)
Scheduling is the timing of an operating activity . scheduling includes activities allocate facilities , equipment or labor like an operation and determine the order of the operations. When this has been developed various methods in production scheduling, among other production scheduling priority to working time in advance in order of production processes, scheduling based on the number of existing machines and production scheduling based on stable production rate setting fora variety of inventory levels to meet consumer demand .Methods Campbell - Dudek - Smith (CDS) , the method is basically solve the problem of n jobs on m machines flow shop. In this scheduling attempted to get the price of the smallest make span of (m - ) the possibility of scheduling . with the price of the smallest make span scheduling a sequence of jobs that most excellent workmanship .Based on the data obtained from the results of research conducted at PT . Triangle Motorindo for production scheduling using CDS known that scheduling method to be applied in PT . Triangle Motorindo Semarang CDS method is based on the total make span is 23.1 hours and the efficiency of which is 35.26 %.Keywords : CDS , makespan , efficiency